“Unfaithful Children Are Waiting for your Help.” The Image of the Colonized Other in Spanish Advertising Posters: Uses, Contexts and Artistic References - Quintanar Cabello, Vanessa (Hispania Nova, 2023)
At the end of the 19th century, one of the visual languages with the greatest impact until after World War II was born in Europe: the advertising poster. Thanks to this support, products and services were made known, but also social and political ideas, as well as stereotypes about certain groups. Through this article it is proposed to analyze the figure of the colonized Other in the Spanish advertising poster, to verify the contexts in which it is inserted, the objects with which it is associated and its evolution parallel to the process of Spanish decolonization throughout the twentieth century. To this end, the collection of advertising posters of Carlos Velasco Murviedro, the largest private collection in Spain of this type of document, will be taken as the basis of analysis.